CT-CFD integrated investigation into porosity and permeability of neat early-age well cement at downhole condition. (30th April 2019) - Yang, Xinxiang; Kuru, Ergun; Gingras, Murray; Iremonger, Simon
Graphical abstract: Highlights: Minimum RVE size of cement should be determined individually for flow simulation. Permeability of early-age Class G cement can be correlated with effective porosity. Early-age Class G cement exhibits similar poroperm behavior with tight sandstone. Abstract: This study presents an experimental and numerical approach to investigate the permeability of neat early-age (7 days) well cement sample under downhole conditions (50 °C and 10 MPa). Realistic representative volume elements (RVEs) were first extracted from Class G cement sample. Porosity and permeability (poroperm) of the RVEs were then calculated through combining computed tomography (CT) with three-dimensional (3D) computational fluid dynamics (CFD) technique. In the end, poroperm data of well cement and formation rocks were compared. Results show that 1) at the micron scale (2.64 µm), non-uniform porosity distribution in cement sample was observed, which caused the permeability disparities at different locations. The minimum RVE size should be determined on a case-by-case basis. The characteristic linear curve-fitting line was generated to correlate the permeability with the effective porosity. 2) Average effective porosity values calculated from the representative element volumes were introduced into the correlation curve to determine the permeability of cement sample. From the simulation, the permeability of the neat early-age Class G cement sample at downhole condition was estimated to be 9.771 × 10 −17  m 2 . 3) Juxtaposed with poroperm experiment data of different formation rocks, the poroperm of neat early-age well cement are mainly distributed in the sandstone zone, which suggests that the permeability of neat early-age cement is close to permeability of tight sandstone formations. The linear relationship between poroperm of neat early-age well cement sample in semi-log plot indicates its permeability behavior will approach to that of shale if the hydration process of cement is continued.